Peningkatkan Kemampuan Guru dalam Pembelajaran Kooperatif Model Student Teams Achieverment Divisions Melalui Kelompok Kerja Guru Di Sdn Getas II - Fahruddin, Muh (Ridwan Institute, 2021)
This study aims to determine the increase in the ability of teachers to apply the Student Teams Achieverment Divisions (STAD) model of cooperative learning through the Kelompok Kerja Guru (KKG) or teacher working group activities at SD Negeri Getas II, Playen sub-district in 2020. This research used the School Action Research design. The research subjects were teachers in grades I, II, III, IV, V, VI, teachers of Islamic Religious Education subjects, and teachers of Physical Education at SD Negeri Getas II in Playen sub-district in 2020. Data collection was through observation of teachers' abilities in applying the Student Teams Achieverment Divisions (STAD) model of cooperative learning through school teacher working group activities and assessment of the results of learning actions. Meanwhile, the data analysis used is descriptive qualitative analysis. The results showed an increase in the ability of teachers to apply the Student Teams Achieverment Divisions model of cooperative learning through the teacher working group activities of SD Negeri Getas II, sub-district Playen in 2020 which was marked by an increase in the value obtained between before being subjected to action and after being subjected to action. The value of the teacher's ability to apply the Student Teams Achieverment Divisions (STAD) model of cooperative learning has increased. Before being subjected to the action, only 60% of teachers got good grades. After being subjected to the action, the teacher's ability score at the end of the first cycle got a mean score of 81.47 in the Good category, and at the end of the second cycle the teacher's score got an average score of 87.30 in the Good category.